Effects of Zirconium Doping Into a Monoclinic Scheelite BiVO4 Crystal on Its Structural, Photocatalytic, and Photoelectrochemical Properties - Ikeda, Shigeru; Kawaguchi, Takato; Higuchi, Yui; Kawasaki, Naoto; Harada, Takashi; Remeika, Mikas; Islam, Muhammad M.; Sakurai, Takeaki (Frontiers in Chemistry, 2018)
Effects of zirconium (Zr) doping into BiVO4 powder on its structural properties and photocatalytic activity for O2 evolution were examined. The formation of BiVO4 powder crystallized in a monoclinic scheelite structure (ms-BiVO4) was achieved when the sample was doped with a relatively small amount of Zr. The photocatalytic activity of Zr-doped ms-BiVO4 powder was much higher than that of non-doped ms-BiVO4. However, further doping caused a reduction of photocatalytic activity for O2 evolution due to the occurrence of structural alterations into tetragonal scheelite and tetragonal zircon structures. Similar effects of Zr doping were also observed for the photoelectrochemical (PEC) system based on BiVO4 thin films doped with various amounts of Zr. Thus, Zr doping was confirmed to be effective for improvements of photocatalytic and PEC functions of BiVO4 for water oxidation.